Longitudinal changes in total body creatine pool size and skeletal muscle mass using the D3‐creatine dilution method. Issue 3 (25th June 2013) - Stimpson, Stephen A.; Leonard, Michael S.; Clifton, Lisa G.; Poole, James C.; Turner, Scott M.; Shearer, Todd W.; Remlinger, Katja S.; Clark, Richard V.; Hellerstein, Marc K.; Evans, William J.
Abstract : Background: We recently validated in cross‐sectional studies a new method to determine total body creatine pool size and skeletal muscle mass based on D3 ‐creatine dilution from an oral dose and detection of urinary creatinine enrichment by isotope ratio mass spectrometry (IRMS). Routine clinical use of the method in aging and disease will require repeated application of the method, with a more widely available technology than IRMS, to enable determination of change in skeletal muscle mass in longitudinal studies. We therefore adapted the method to liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) technology, and sought to establish proof of concept for the repeated application of the method in a longitudinal study. Because the turnover of creatine is slow, it was also critical to determine the impact of background enrichment from an initial dose of oral D3 ‐creatine on subsequent, longitudinal measurements of change in muscle mass. Methods: Rats were given an oral tracer dose of D3 ‐creatine (1.0 mg/kg body weight) at 10 and 17 weeks of age. LC‐MS/MS was used to determine urinary D3 ‐creatine, and urinary D3 ‐creatinine enrichment, at time intervals after D3 ‐creatine administration. Total body creatine pool size was calculated from urinary D3 ‐creatinine enrichment at isotopic steady state 72 h after administration of D3 ‐creatine tracer. Results: At 10 weeks of age, rat lean body mass (LBM) measured by quantitative magnetic resonance correlated with creatine pool size ( r  = 0.92, P  = 0.0002). Over the next 7 weeks, the decline in urinary D3 ‐creatinine enrichment was slow and linear, with a rate constant of 2.73 ± 0.06 %/day. Subtracting background urinary D3 ‐creatinine enrichment from the elevated enrichment following a second dose of D3 ‐creatine at 17 weeks permitted repeat calculations of creatine pool size. As at 10 weeks, 17‐week LBM correlated with creatine pool size ( r  = 0.98, P <0.0001). In addition, the change in creatine pool size was correlated with the change in LBM during the 7 weeks of rat growth between measurements ( r  = 0.96, P <0.0001). Conclusion: The LC‐MS/MS‐based D3 ‐creatine dilution method can be applied repeatedly to measure total body creatine skeletal muscle mass change in longitudinal study.